Evaluasi Fungsi Ekologis Taman Kota pada Lanskap Riparian Sungai Cimanuk, Indramayu - Aziizah, Nidaa Aditya; Budiarti, Tati (Jurnal Lanskap Indonesia, 2024)
The riparian landscape of the Cimanuk River has been declared a local protected area. Cimanuk Park is located on the northern coast of Java Island, Indramayu Regency which is one of the tourist centers and icons of the city of Indramayu. City parks are closely related to ecological functions that affect user comfort. This study aims to identify the diversity of vegetation, evaluate ecological functions, determine the perception of the people of Indramayu towards Cimanuk Park which is used as an icon of the city of Indramayu and provide recommendations for improving the green system of Cimanuk Park. The method of this research uses the study of aspects of ecological functions including microclimate measurement, and noise level measurement, which consists of preparation, inventory, analysis, assessment and evaluation, and preparation of recommendations. It has 17 species with a total of 333 individuals. This study conducted an assessment of vegetation diversity using the KPI method. Most of Cimanuk Parks have good categories in modifying temperature and controlling air humidity and have moderate categories in resisting wind, and reducing noise. Meanwhile, from the results of the study, the THI value was in the uncomfortable category.